Characterization of revenue equivalence - Birgit Heydenreich; Rudolf Müller; Marc Uetz (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2007)
The property of an allocation rule to be implementable in dominant strategies by a unique payment scheme is called revenue equivalence. In this paper we give a characterization of revenue equivalence based on a graph theoretic interpretation of the incentive compatibility constraints. The characterization holds for any (possibly innite) outcome space and many of the known results about revenue equivalence are immediate consequences.
Keywords: 330